2020
DOI: 10.1017/s0950268820000813
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hospitalised paediatric community-acquired pneumonia and bacterial pneumonia following the introduction of 13-valent pneumococcal conjugate vaccine in the national immunisation programme in Japan

Abstract: Studies on community-acquired pneumonia (CAP) and pneumococcal pneumonia (PP) related to the 13-valent pneumococcal conjugate vaccine (PCV13) introduction in Asia are scarce. This study aimed to investigate the epidemiological and microbiological determinants of hospitalised CAP and PP after PCV13 was introduced in Japan. This observational hospital-based surveillance study included children aged ⩽15 years, admitted to hospitals in and around Chiba City, Japan. Participants had bacterial pneumonia based on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…However, the majority of H. influenzae isolated from respiratory specimens were non-typeable strains. Therefore, the influence on antimicrobial susceptibility is not strong compared with S. pneumoniae [14]. Regarding the susceptibility of individual antibiotics, the results showed no significant changes in those in the recent past.…”
Section: Discussionmentioning
confidence: 78%
“…However, the majority of H. influenzae isolated from respiratory specimens were non-typeable strains. Therefore, the influence on antimicrobial susceptibility is not strong compared with S. pneumoniae [14]. Regarding the susceptibility of individual antibiotics, the results showed no significant changes in those in the recent past.…”
Section: Discussionmentioning
confidence: 78%
“…In children and adolescents, PCV7 and PCV13 serotypes were also reported to be prevalent before 2010 (66.7% [ 39 ]–100% [ 40 ] among IPDs and 49.3% [ 41 ]–69.1% [ 42 ] among all other PDs for PCV7 serotypes; 81.0%–100.0% [ 39 ] among IPDs and 70.6% [ 41 ]–83.2% [ 42 ] among all other PDs for PCV13 serotypes). Similar to children, after the introduction of PCV7 and PCV13 in 2013, the vaccine-type serotypes also became less prevalent (0.0% [ 25 , 34 , 36 , 43 ]–2.3% [ 44 ] among IPDs and 0.0% [ 45–48 ]–7.1% [ 49 ] among all other PDs for PCV7 serotypes; 0.0% [ 25 ]–20.0% [ 34 ] among IPDs and 6.2% [ 47 ]–30.0% [ 45 ] among all other PDs for PCV13 serotypes). When considering nationwide and multi-prefectural studies only, PCV7 and PCV13 serotypes among IPDs before 2010 were reported to be 71.8% [ 27 ]–75.4% [ 50 ] and 93.7% [ 50 ], but decreased to 0.0% [ 36 ]–2.3% [ 44 ] and 7.0% [ 36 ]–17.2% [ 44 ] after 2013, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a longitudinal study in Taiwan reported increases in penicillin resistance rates for PCV13 serotypes 19F and 19A in 2016, after reporting declining penicillin resistance rates between 2012 and 2014 [64]. Similarly, a recent study in Japan in children aged \ 5 years hospitalized for CAP reported an increase in penicillin G resistance for nonvaccine serotypes 15A and 35B between 2016 and 2018 [68]. Several factors could be responsible for these increases in antibiotic resistance, including rampant use of antimicrobials in healthcare settings in addition to the spread of antimicrobial-resistant bacterial strains [38].…”
Section: Discussionmentioning
confidence: 98%
“…In Japan, following the introduction of PCV13 in 2013, one study reported that the annualized incidence of hospitalized CAP in children aged \ 5 years decreased from 14.3 per 1000 children in 2012 to 9.7 per 1000 children in 2018 [68]. Specifically, the incidence of CAP due to vaccine serotypes 1, 3, 7F, and 19A decreased in the years following the introduction of PCV13 in Japan; an overall decrease in the prevalence of all PCV13 serotypes from 30% to 13% was observed during this period [68]. Overall, reductions in IPD incidence and CAP in other Asian countries demonstrate successful implementation of vaccination programs against S. pneumoniae and may serve as a model for the Philippines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation